THE INFLUENCE OF FRIENDSHIP AND RELIGIOUS COMMITMENT ON ISLAMIC CHARACTER AMONG STUDENTS AT UNIVERSITI UTARA MALAYSIA - Muhibbi, Moh. Saddad; Rohmatulloh, Ulul Azmi Nur; Busthami Nur, Abdul Hamid; Salsabila, Sari (Sekolah Tinggi Agama Islam Al Hidayah, 2025)
Background: Morality and character education remain critical concerns in Malaysia, with growing evidence of moral degradation among youth. Prior studies report inconsistent findings on the role of friendship, while research on religious commitment remains limited in the Malaysian context. Purpose of the Study: This study investigates the influence of friendship quality and religious commitment on students’ Islamic character. Methods: Using a quantitative correlational design, data were collected from 380 respondents and analysed using partial least squares structural equation modelling (PLS-SEM) with SmartPLS 4.0 software. Findings: The results indicate that friendship has a positive but modest effect on students’ Islamic character (effect size = 0.022), whereas religious commitment shows a substantially stronger influence (effect size = 0.208). Together, both variables explain 33% of the variance in Islamic character (R² = 0.330). These results highlight that while peer interactions contribute to character development, internal religious commitment plays a primary role. Conclusions: These findings highlight the importance of institutional support for religious engagement in higher education, even in non-religious universities like Universiti Utara Malaysia. Measures such as creating supportive environments for religious practice, promoting ethical reflection, and setting clear boundaries for social interactions can help maintain and strengthen students’ Islamic values while guiding peer relationships and preventing negative external influences. Future research is recommended to explore the remaining 67% of unexplained variance as potential factors.